Beyond Modernism: Toward a New Myth Criticism - Ted R. Spivey (Oz, 1991)
The most important single document concerning myth and literature in twentieth century writing in English is undoubtedly T. S. Eliot's review of James Joyce's Ulysses in The Dial of November, 1923. In it Eliot announced that something he called "the mythical method" would replace the narrative method and would lead to a new order and form in literature.